Determination of Calibration X-Ray Beam Qualities and Establish a Set of Conversion Coefficients for Calibration of Radiation Protection Devices Used in Diagnostic Radiology - Siddiqua, Tanjim; Rahman, Md. Shakilur; Sanaullah, Md.; Mitu, Zohora Akter; Hossain, Imran; Rubai, Sadeka Sultana (East European Journal of Physics, 2021)
The use of X-ray facilities in calibrating radiation measuring equipment in diagnostic radiology requires an exact knowledge of the radiation field. X-ray spectrums are made narrow beam by proper filtration recommended by several international organizations. In the present study, the experimental determination of X-ray calibration qualities and analysis of conversion coefficients from air Kerma to ambient and personal dose equivalent is carried for X-ray beam irradiator X80-225kV as per ISO narrow spectrum series at Secondary Standard Dosimetry Laboratory (SSDL) in Bangladesh. The X-ray beam involved in half value layer, effective energy, beam homogeneity coefficient and consistency of X-ray production from the generator (kV and mA) is conducted. A discrepancy of half value layer has been observed for N200 beam code by -8.5% which leads to the deviation of effective energy by -7.7% with a standard deviation of 1.3%. The conversion coefficients from the air kerma to dose equivalent that satisfying the condition of ICRU sphere is established to obtain radiation qualities and compared with values referred by other standard laboratories. A deviation of 0.87% has been observed for H*(10) and H¢(0.07) in between ISO and BCRU empirical relation which is insignificant. A set of conversion coefficients for Hp(10) and Hp(0.07) has also been calculated for ICRU four element tissue.